Spiritual intelligence and its relationship to perceived academic self-efficacy for university students - Obaid Mohammed, Salma (Opción, 2019)
The present study aimed to identify the level of spiritual intelligence among the students of the university and its relation to the academic self-efficacy in the light of the variables of gender and specialization. And to identify the differences between students in the spiritual intelligence and in the academic self-efficacy perceive of the variables of type and specialization, as well as to identify the correlation relationship and diffe- rences in this correlation between the two current research variables. In order to achieve the research objectives, the researcher constructed two measurements for the current study and verified their validity. The validity of the measurements was verified and the validity of the measurements was calculated by the method of retesting and the Vaccronbach method. After completion of the two measurements, after collecting and processing the data statistically, the researcher reached several results, among which the most important were the following: - The current research sample of university students enjoy a high level of spiritual intelligence. - The current research sample of university students enjoys a high level of academic perception. - There are no statistically significant differences in spiritual intelligence according to gender and specialization variables. - There were no statistically significant differences in academic self-efficacy according to gender variable. - The existence of differences of statistical significance in the academic self-competence perceived among students according to the variable of specialization (scientific, human) and was in favor of scientific specializa- tion. The existence of a positive correlation between positive and cognitive self- efficacy based on the responses of the sample as a whole, gender, specializa- tion. In light of the research results, the researcher recommended a number of recommendations, including: - Work on developing scientific curricula in order to achieve development and growth in the spiritual intelligence and the level of academic self-efficacy among students since the first stages of education and in accordance with the age of mental them. The researcher suggested a number of proposals, including: 1. To benefit from the two parameters that the researcher has built for the purposes of this study as research tools in subsequent studies. 2. Conducting a comparative study between developmental stages.